Experimental Study of a Pneumatic Separator. Issue 1 (September 2021) - Chernyakov, A V; Koval, V S; Begunov, M A; Algazin, D N; Petrov, N V
Abstract: The article provides information on the relevance of grain cleaning in modern agricultural production. A model of a new pneumatic centrifugal grain separator is proposed. Experiments have been carried out to determine the quantitative and qualitative indicators of the separator's operation. The dependences of the completeness of separation and grain losses on the supply and the resulting air velocity have been obtained. The analysis of the obtained dependencies is carried out and recommendations are given on the use of the separator and its rational modes for preliminary, primary and secondary cleaning of grain.